AUTO NEWS PROGRAMS FOR TAKING WWW.PLASA.COM - Aji Priambodo; Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2002)
PT. Telekomunikasi Indonesia, through Multimedia Division to improve servicewww.plasa.com site. One is a feature that will display news clippings. This featureallows visitors to the site www.plasa.com get the latest news stories from severalnews portal in Indonesia.As a partner who is appointed to make this happen, PT Asia Abdijaya Sentosa veryproud to create an automated program that the first news headline makers inIndonesia.Given the complexities in the manufacture of automated programs is very high,sometimes arise in its implementation problems. But hopefully with the skills,abilities and experience that exists, all these obstacles can be overcome, so what willbe displayed on the writing of this study have better benefits to all parties.